The implementation of a green supply chain and its impact on the organizational performance: A case of COATS Bangladesh Limited - Rahman, Md. Muzahidur (Brac University, 2024)
This practicum report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.